2022
DOI: 10.3390/app12115658
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lactobacillus paracasei HII01 Supplementation on Performance in Attention (Go/No-Go) Tasks and Quinolinic Acid and 5-Hydroxyindoleacetic Acid Levels in Thai Children—A Preliminary Study

Abstract: Cognitive development is defined as the capacity of a child to think, reason, and use language, which are all vital to their overall growth. Attention deficit/hyperactivity disorder (ADHD) is the most common neurodevelopmental disorder. Though several factors are associated with the incidence of ADHD, gut microbiota and gut homeostasis play critical roles in it. Gut dysbiosis and altered gut homeostasis are linked to several physical and psychological complications that affect gut–brain communication (the gut–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A preliminary study on the cognition of children in Thailand found that Lactobacillus paracasei HII01 increased the levels of HIAA in urine after 12 weeks of supplementation and the attention state of children significantly improved. 62 Additionally, the decreased levels of ZO-1 and Ocln indicated that DSS exposure caused the tight junctions of the brain to disappear, which indicated the disordered permeability of the blood–brain barrier, 63 and the ZO-1 levels were restored to those of the control group in the Fmb14 group. Alterations in the blood–brain barrier lead to the loss of protection against exposure of the brain to molecules and bacterial metabolites in blood, which may cause damage to astrocytes or pericytes in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study on the cognition of children in Thailand found that Lactobacillus paracasei HII01 increased the levels of HIAA in urine after 12 weeks of supplementation and the attention state of children significantly improved. 62 Additionally, the decreased levels of ZO-1 and Ocln indicated that DSS exposure caused the tight junctions of the brain to disappear, which indicated the disordered permeability of the blood–brain barrier, 63 and the ZO-1 levels were restored to those of the control group in the Fmb14 group. Alterations in the blood–brain barrier lead to the loss of protection against exposure of the brain to molecules and bacterial metabolites in blood, which may cause damage to astrocytes or pericytes in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Most important, consistent and prolonged administration will be necessary to draw strong conclusions about probiotic effects on cognitive outcomes. Indeed, such studies are warranted given recent evidence pointing to probiotic effects on attention tasks in Thai children (6-12-year-olds) after prolonged (12 weeks) administration 49 . Moreover, multiple reviews published since this study was conducted have found evidence for a potential role of probiotics and prebiotics in improved cognitive function in humans [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…Specific nutritional factors have been shown to influence quinolinic acid levels and reduce quinolinic induced damage. These include probiotics (65) , polyphenols (66) and essential fatty acids (67) . Assessing intake of these dietary components may therefore be valuable.…”
Section: The Role Of Metabolic Factors In Depressionmentioning
confidence: 99%